80‐3: All Organic Layers Inkjet Printed OLEDs with a Printable Electronic Transport Layer. Issue 1 (29th May 2019) - Wang, Shipan; Wu, Yuan-Chun; Jiao, Shibo; Shi, Ting; Ai, Na; Zhang, Yunan; Iguchi, Shinsuke; Lu, Po-Yen; Zhou, Hang
Abstract : All organic layers inkjet printed OLEDs have been successfully developed with a printable electronic transport layer (ETL). A jettable ETL ink was prepared with a commercially soluble electronic transport material and alcohol solvents. Based on orthogonal solvent systems, the deposition of ETL caused little damage to the emission under‐layer. And ETL printed OLEDs show comparable performance with its evaporation ETL counterparts.